(3GdCQHYhf MOjKG eY GdTQM hGdHjGfs - (3GdYGedj, HgGA GdOjf, HgGA GdOjf GdYGedj, eMeO Hf MSjf Hf YHO GdUeO, J (B1031(3g` (B1622(3es ((3eMeO EHQGgje Hf eMeO Jbjs)
(3ChdgG (B:s
(3ChdgG(B: (3Ef CMSf MOjK jJMdi GddSGf HLhGgQ MbGFbg hNjQ NHQ JLdi GdEfSGf aj RhGgQ MOGFbg (B... (3gPG CQHYhf MOjKG ef WQb Cgd HjJ GdfHhI (B... (3LeYJgG ef CeGcfs
(3BNQgG (B:s
(3BNQgG(B: (3Edjc ef NaGjG EdgjGJ GdadcjI aMbjb Cf JUOb ChdFc CjVG ajeG jJdhfg Ydjc ef NHGjG GdYhGde GdbOSjI GdedcjI hgfG CbWY GdcdGe(B. (3TGcQG Ydi Jhajbg ddEJeGe heUdjG Ydi CTQa GdCfGes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B6: 102s
(3GdPQjYI, L (B1: 261s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdMOjK hGdeUWdMs